Pengajaran Dalam Gereja Di Kelas Katekesasi Menurut Kisah Para Rasul 2:42 - Banunaek, Serli Susanti (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2024)
The aim of this research is to explore and understand the important role of teaching in the church context, especially in catechesis classes, as outlined in Acts 2:42. The research approach consists of an exegetical method that involves analyzing the text of Acts 2:42 from historical, cultural and theological perspectives. In addition, the library study method is used to examine teaching concepts within the framework of theology and church practice through related scientific books and journals. The research results show that teaching in catechesis classes has a significant impact in building the foundation of faith, strengthening the church community, and directing spiritual growth. The practical implications of these findings can be used as a guide to strengthen the role of teaching in the formation of religious identity and spiritual growth in church communities.